Effects of repeated transection and coaptation of peripheral nerves on axonal regeneration and motoneuron survival. Issue 8 (August 2019) - Zhou, Sizheng; Wu, Min; Chen, Gang; Tremp, Mathias; Kalbermatten, Daniel; Wang, Wei; Wang, Wenjin
Abstract: Background and purpose: Salvage procedures for facial reanimation can involve a second neurorrhaphy operation. It remains unclear whether reuse of the original donor nerve in the salvage procedure remains likely to produce successful outcome. This study aimed to investigate the effect of repeated transection and coaptation of a nerve on axonal regrowth and motoneuron survival. Materials and methods: The sciatic nerves of Sprague Dawley rats were transected and microsutured once (the one-time group) or repeatedly at eight-week intervals (the repeated group), and the animals remained alive for eight weeks before sacrifice. The gastrocnemius muscle was weighed, and muscle fiber diameter was measured with hematoxylin-eosin staining. Axonal count of the distal nerve stump was calculated by toluidine blue staining. Myelin thickness and axonal diameter were analyzed by transmission electronic microscopy. Finally, motoneurons were retrogradely traced to the spinal cord using Fluoro-Gold. Results: Repeated coaptation of nerves resulted in significant decreases of the wet weight ratio of gastrocnemius and muscle fiber diameter. The axonal counts and myelin thicknesses of the distal stumps were comparable between the groups, whereas axonal diameter was significantly smaller after repeated injury. Additionally, retrograde tracing demonstrated significantly less motoneurons in the L4–L6 spinal segments of the repeatedly injured animals than that of the one-time group. Conclusions: Compared with one-time nerve injury, repetitive transection and coaptation of nerves resulted in compromised axonal regeneration, motoneuron survival, and target muscle recovery. It is possible that the final functional outcome could also be compromised, and the patients should be counseled accordingly.